An Overview Of Population Trends And Pattern Of Nepal - Chhabilal Acharya (Journal of Contemporary Review, 2025)
Population growth is increase in the number of individuals in a population. Nepal’s trend of population growth shows a fluctuating rate till 2021 Population Census. It has sharply decreased during 2001 – 2021 census period remaining 0.92 percent per annum. As per the 2021 census, Nepal’s population stood at 29.2 million, which is an increase of 2.8 million when compared to the 26.4 million population recorded in the 2011 census. The population has increased during the past decade, with an average annual growth rate of 0.92%, lower than the 1.35 % growth rate reported in the 2021 census. On the other hand of state population growth rate is unequal to each other.